Manufacturing process of short carbon fiber reinforced Al matrix with preformless and their properties - Yongbum Choi (Nature Portfolio, 2021)
Abstract The conventional manufacturing process of fiber-reinforced metal matrix composites via liquid infiltration processes, preform manufacturing using inorganic binders is essential. However, the procedure involves binder sintering, which requires high energy and long operating times. A new fabrication process without preform manufacturing is proposed to fabricate short carbon fiber (SCF)-reinforced aluminum matrix composites using a low-pressure infiltration method. To improve the wettability between fiber and matrix, fibers were plated copper using an electroless plating process. The low-pressure infiltration method with preformless succeeded in manufacturing a composite with a volume fraction of about 30% of carbon fibers.The fiber orientation of the composite material manufactured without preform and the fiber orientation of the composite material manufactured using an inorganic binder was almost the same. The manufactured composites with preformless have high hardness and high thermal conductivity.